Survival among people with down syndrome: a nationwide population-based study in denmark - Zhu, Jin Liang (Genet Med, 2012)
PURPOSE: Several studies have shown substantially longer survival among persons with Down syndrome in recent decades. We examined survival patterns among Danish persons with Down syndrome by karyotype. METHODS: A national cohort of 3,530 persons with Down syndrome identified from the Danish Cytogenetic Register and a reference cohort of persons without Down syndrome randomly selected from the general population were followed from 1 April 1968 to 15 January 2009 by linkages to the Register of Causes of Death and the Civil Registration System. RESULTS: Overall, persons with Down syndrome had higher mortality than the reference cohort but to a lesser degree for persons with mosaic trisomy 21 than for persons with standard trisomy 21 or with Robertsonian translocations (hazard ratio 4.98 (95% confidence interval 3.51–7.08), 8.94 (8.32–9.60), and 10.23 (7.50–13.97), respectively). Among persons with Down syndrome born after April 1968, more recent birth cohorts had lower mortality rates than older birth cohorts, which was largely due to declining mortality among persons with Down syndrome who also had congenital heart defects. CONCLUSION: Recent birth cohorts of persons with Down syndrome experienced declining mortality, likely due to treatment for congenital heart defects, and persons with mosaic trisomy 21 had better survival than persons with other Down syndrome karyotypes.